2009
DOI: 10.1111/j.1365-2249.2009.03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of treatment using interleukin-2 in a patient with idiopathic CD4+ lymphopenia andMycobacterium avium-intracellulare

Abstract: SummaryWe present the case of a 39-year-old white man with a Myobacterium aviumintracellulare pulmonary infection found to have a CD4+ count of 172 cells/ mm 3 and diagnosed subsequently with idiopathic CD4 + lymphopenia (ICL). After receiving clathromycin for 4 months with minimal improvement, the patient was started on pegylated subcutaneous interleukin (IL)-2 at 600 000 units daily. Later, he received incrementally higher pegylated IL-2 doses until he reached a maintenance dose 3 months later of 11 million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Limited data from those reports support IL-2 as a relatively safe and potentially effective treatment for ICL patients with opportunistic infections, especially when combined with conventional treatment regimens. [30507293101]…”
Section: Pathogenesismentioning
confidence: 99%
“…Limited data from those reports support IL-2 as a relatively safe and potentially effective treatment for ICL patients with opportunistic infections, especially when combined with conventional treatment regimens. [30507293101]…”
Section: Pathogenesismentioning
confidence: 99%
“…Severe CD4+ T cell lymphopenia is also observed in idiopathic CD4+ T lymphopenia (ICL; [31][32][33][34][35]. It is possible that our patients might be ICL and selective IgM deficiency is a co-incidental finding.…”
Section: Discussionmentioning
confidence: 75%
“…It is possible that our patients might be ICL and selective IgM deficiency is a co-incidental finding. However, it appears unlikely since ICL patients have either normal level of immunoglobulins [31][32][33], low IgG and IgA [34], or increased IgA [34], but IgM levels are normal. Furthermore, MAC infection was present in all three patients described here, whereas in ICL, Cryptococcus and mycobacterial tuberculosis are most common infections, and only a few cases of MAC infection have been reported [31,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…Three of these had resistant wart infections; a fourth had long-term IL-2 treatment for pulmonary mycobacterial infection, which completely resolved. 12,30 Regent et al 11 treated 6 patients with IL-2 and observed that patients with responses to IL-2 treatment in vivo showed improved lymphocyte counts. 11 Long-term IL-2 also has been used as successful management of cytomegalovirus retinitis in ICL.…”
Section: Discussionmentioning
confidence: 99%
“…31 Other studies have reported success with recombinant IL-2 with or without interferon-γ. 22,30,32,33 IL-7 also has attracted attention, because impaired CD4 T-cell responses to IL-7 in ICL might contribute to cell depletion 34 ; this cytokine was used in an open-label phase I and IIa clinical trial and 1 case of progressive multifocal leukoencephalopathy in ICL, with some benefit. 35,36 The choice of subjects for cytokine therapy and the parameters to be used for follow-up are unclear and further studies would be required to evaluate efficacy.…”
Section: Discussionmentioning
confidence: 99%